Application of micro‐solid‐phase extraction for the on‐site extraction of heterocyclic aromatic amines in seawater. Issue 7 (1st February 2018) - Basheer, Chanbasha
Abstract: An efficient on‐site extraction technique to determine carcinogenic heterocyclic aromatic amines in seawater has been reported. A micro‐solid‐phase extraction device placed inside a portable battery‐operated pump was used for the on‐site extraction of seawater samples. Before on‐site applications, parameters that influence the extraction efficiency (extraction time, type of sorbent materials, suitable desorption solvent, desorption time, and sample volume) were investigated and optimized in the laboratory. The developed method was then used for the on‐site sampling of heterocyclic aromatic amines determination in seawater samples close to distillation plant. Once the on‐site extraction completed, the small extraction device with the analytes was brought back to the laboratory for analysis using high‐performance liquid chromatography with fluorescence detection. Based on the optimized conditions, the calibration curves were linear over the concentration range of 0.05–20 μg/L with correlation coefficients up to 0.996. The limits of detection were 0.004–0.026 μg/L, and the reproducibility values were between 1.3 and 7.5%. To evaluate the extraction efficiency, a comparison was made with conventional solid‐phase extraction and it was applied to various fortified real seawater samples. The average relative recoveries obtained from the spiked seawater samples varied in the range 79.9–95.2%.